Load limiting control design for rotating blade root pitch link load using higher harmonic LTI models - Mballo, C.E.; Prasad, J.V.R. (My University, 2018)
This paper discusses the synthesis of a load limiting controller (LLC) for critical helicopter components that are subjected to significant fatigue loading. The development of a (structural) load limit violation detection and limit protection algorithm using a linear time invariant (LTI) model of helicopter coupled body/rotor/inflow dynamics is described. The developed load limiting controller is evaluated in its ability to limit harmonic pitch link loads and its impact on maneuver performance for a typical longitudinal doublet input.